Tackling a long‐standing problem: Typification of Orthotrichum crispum, Ulota crispula and Ulota intermedia (Bryopsida: Orthotrichaceae). Issue 4 (15th August 2016) - Caparrós, Rut; Garilleti, Ricardo; Price, Michelle J.; Mazimpaka, Vicente; Lara, Francisco
Abstract: Previous taxonomic studies on the Holarctic species of Ulota, including both morphological and molecular approaches, distinguished Ulota crispa, U. crispula and U. intermedia as separate taxa worthy of recognition at the specific level, instead of belonging to a single, highly variable species ( U. crispa ). Available original material for these three names has been studied and in several cases these are heterogeneous, containing two or even three of these closely related species. We discuss the nomenclatural history of each species and the extant original specimens from which lectotypes for Orthotrichum crispum, Ulota crispula and U. intermedia are designated.